Prototypes of Very High Fidelity, Accessibility, and Reusability with Laum - Oliveira, Francisco; Batista, Rootedy; Araujo, Thiago; Morais, Breno; Oliveira, Deivith (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais Estendidos do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas ComputacionaisDO - 10.5753/ihc_estendido.2023.233185, 2023)
This paper presents LAUM, a library of micro frontends (MFE) with very high usability and accessibility. LAUM's components are made available in design time via the Figma plugin. LAUM narrows the gap between designers and developers, making highly reusable components discoverable at design time. Accessibility is a given since it is built into all components. Early testing is assured by the plugin's HTML generator (accessible html + MFE calls).